Weakly supported voltammetry - Limon Petersen, J; Juan Gualberto Limon Petersen (2010)
This thesis is concerned with dynamic electrochemical experiments with different concentrations of supporting electrolyte. Normally supporting electrolyte is added to a solution in order to avoid undesirable effects as migration and potential drop in solution. However, in the present thesis we focus on the study and understanding of such effects as the concentration of supporting electrolyte decreases. First a theoretical treatment is proposed, based on numerical simulation using the Nernst-Planck- Poisson system of equations. The theoretical treatment is compared with previous works as electroneutrality, the differences between both models are explained. The model is also compared with theoretical results to validate the theoretical treatment. Experimental results of chronoamperometry and cyclic voltammograms are compared with theoretical results obtaining remarkable agreement. Is noteworthy that to the best of the author’s knowledge this is the first time that experimental dynamic voltammetry under weakly supported conditions has been successfully modeled by a theoretical treatment. The electrochemical reaction of a non-charged electroactive species is presented for the system ferrocene/ferrocenium in acetonitrile in which the oxidized and reduced species are soluble in solution, the reaction is studied at different concentrations of supporting electrolyte. Comparison is presented between theoretical simulations and experimental results, for which potential drop in solution is studied. Then systems involving charged electroactive species are treated, in these cases the decrease of supporting electrolyte influence the mass transport of the electroactive species due to migration, comparison between different experimental systems as hexaammineruthenium (III)/(II), cobaltoceniun/cobaltocene and hexacyanoferrate (III)/(II) are presented in comparison with theoretical simulations. More complex mechanistic paths are also investigated, such as deposition and stripping, in which it is established that the level of support required to achieve ‘diffusion only’ voltammetry is on dependence of the concentration of amalgamated electroactive species prior to the stripping step. Comparison between theoretical simulation and experimental results of the deposition and stripping of thallium at a mercury hemisphere are presented, and found to be in good agreement for either chronoamperometry and cyclic voltammetry Simulations are also presented showing the necessary required amount of supporting electrolyte required to achieve ‘diffusion only’ cyclic voltammetry. This is obtained by comparison between diffusion only software and the simulation described in the present thesis. The required amount of supporting electrolyte is shown to depend on the concentration of the electroactive species and supporting electrolyte in the media, the electrode radius, the diffusion coefficient of species and the scan rate. Finally, the cyclic voltammetry in weakly supporting media is used to obtain mechanistic information, by using the migration of electroactive species to differentiate the mass transport of electroactive species to the electrode. The two single electron reductions of anthraquinone in acetonitrile is presented, and the comproportionation mechanistic path is observed in weakly supported media, diffusion only voltammetry is normally unable to present whether this mechanism path takes place, due to the similarity in diffusion coefficients of the electroactive species. In contrast in weakly support conditions the diffusion controlled comproportionation mechanistic path is observed experimentally and constraints for the rate constant are discussed.